Effects of transportation on cattle health and production: a review. (21st November 2018) - Van Engen, N. K.; Coetzee, J. F.
Abstract: The goal of this review is to present a concise and critical assessment of the literature related to physiologic responses in cattle that are subjected to transportation. Over two-thirds of US cattle are transported. Understanding trends in circulating physiologic parameters is an important part of mitigating the negative effects of transportation. For the producer, linking these effects after transportation to morbidity outcomes within the first 45 days on feed (i.e. especially development of bovine respiratory disease) is critical. Physiologic parameters in circulation are of primary importance and may have value for prediction of bovine respiratory disease on arrival and for the understanding of disease pathogenesis. The results of our literature survey indicated that post-transportation immune function, increased acute phase proteins, glucocorticoids, and inflammation are a pivotal starting point for understanding disease. These potential biomarkers may have utility in identifying disease for targeted therapeutics so that traditional protocols that rely heavily on metaphylaxis can be avoided. Additional research is needed to develop strategies for physiological marker identification, treatment methods, or predictive behaviors to prevent respiratory disease before and after transport. This review examines the significant deleterious effects of transportation handling and stress, and current immune system translation and non-antimicrobial mitigation strategies.